Performance of the PhoP (Rv0757/Mb0780) protein as diagnostic antigen for bovine tuberculosis - Ferrara Muñiz, Ximena; Marques Da Silva, Wanderson; Garbaccio, Sergio Gabriel; Garro, Carlos Javier; Sammarruco, Romina Ayelén; Encinas, Micaela; Carignano, Hugo Adrian; Bianco, María Veronica; Zumarraga, Martin Jose; Cataldi, Angel Adrian; Eirin, Maria Emilia (Elsevier, 2025)
Bovine tuberculosis (bTB), a global zoonotic disease, causes negative effects on human and animal health. PhoP protein is a key regulator of pathogenic phenotypes in members of the Mycobacterium tuberculosis complex, which includes the causative agent of bTB. Despite extensive research on this protein focused in deciphering its regulatory role, little was explored about it as a diagnostic antigen. In humans, a novel role of anti-PhoP antibodies as a possible marker for the diagnosis of TB was demonstrated. However, this issue was not addressed in bovines. In this study, antigenic properties of the PhoP protein were evaluated in naturally Mycobacterium bovis (M. bovis) infected bovines. A high homology of PhoP (≥ 75 %) was observed in environmental mycobacterial species and other genera such as Salmonella and Pasteurella. Using the IFN-gamma release assay (IGRA), we detected cell-mediated immune response against PhoP in cattle from infected herds (25 %; IC 95 % 3.2–65.1), although it was significantly lower than that evoked by the reference antigens, ESAT-6/CFP-10/Rv3615c (75 %; IC95 % 34.9–96.8), and the purified protein derivative (87.5 %; IC 95 % 47.4–99.7) (p < 0.05)). Animals from a bTB free area showed no response against PhoP when analyzed by IGRA. Although, the humoral response detected 62.5 % (CI95% 24.5–91.5) of naturally infected animals, there was 100 % cross-reactivity among TB-free cattle. These results suggest that the PhoP protein is not a promising candidate for bTB diagnosis, due to it had relatively low levels of test sensitivity in the IGRA test, and very low specificity in a humoral antibody western blot assay.